Bone Mineral Density of the Hip and Knee in Children With Spinal Cord Injury - Lauer, Richard (American Paraplegia Society, 2007)
BACKGROUND/OBJECTIVE: To report on the bone mineral density (BMD) of the hip, distal femur, and proximal tibia in children with spinal cord injury (SCI) of at least 1-year duration and before skeletal maturity. METHODS: BMD values were measured in 28 children (age, 9.6 ± 2.5 years; range, 5–13 years) using dual-energy x-ray absorptiometry (DEXA) and were analyzed based on sex, injury, and time since injury. The hip values were compared with reported age- and sex-matched values in children without disability. No comparison was made at the knee because normative data were not available. RESULTS: Average BMD values were 0.48 ± 0.17 g/cm(2) for the total hip, 0.48 ± 0.17 g/cm(2) at the femoral neck, 0.41 ± 0.17 g/cm(2) at the greater trochanter, 0.47 ± 0.17 g/cm(2) at Ward's triangle, 0.38 ± 0.10 g/cm(2) at the distal femur, and 0.37 ± 0.07 g/cm(2) at the proximal tibia. Trends were observed with respect to sex, level of injury, and time since injury. Z-scores for the femoral neck, greater trochanter, and Ward's triangle were −1.65 ± 1.02, −1.83 ± 1.30, and −1.78 ± 0.78, respectively, representing a 40% lower BMD in comparison with children without disability. CONCLUSIONS: Children with a SCI seem to have a substantially lower BMD at the hip and knee in comparison with children without disability, placing them at the same risk for lower extremity fractures as adults with SCI, with potentially higher risks as they age given the lack of activity in a period of their life where exercise is essential for optimal bone health.